Long‐term efficacy and safety of blonanserin in patients with first‐episode schizophrenia: A 1‐year open‐label trial. Issue 12 (7th July 2014) - Ninomiya, Yuriko; Miyamoto, Seiya; Tenjin, Tomomi; Ogino, Shin; Miyake, Nobumi; Kaneda, Yasuhiro; Sumiyoshi, Tomiki; Yamaguchi, Noboru
<x xml:space="preserve">Abstract</x> Aims The purpose of this study was to evaluate the long‐term effectiveness and safety of blonanserin, a second‐generation antipsychotic drug developed in Japan, in patients with first‐episode schizophrenia. Methods Twenty‐three antipsychotic‐naïve patients with first‐episode schizophrenia were treated within an open‐label, 1‐year, prospective trial of blonanserin (2–24 mg/day). Clinical evaluations were conducted at baseline and 2, 6, and 12 months after the start of treatment. The main outcome measures were changes in subjective well‐being and subjective quality of life, as assessed by the Subjective Well‐being under Neuroleptic treatment scale Short form‐Japanese version and the Schizophrenia Quality of Life Scale‐Japanese version, respectively. Secondary outcome measures included the Positive and Negative Syndrome Scale, the Brief Assessment of Cognition in Schizophrenia‐Japanese version, laboratory tests, bodyweight, and extrapyramidal symptoms. Results Fourteen patients (60.9%) remained on the study at 1 year. In the intention‐to‐treat analysis, significant improvements were observed in several subscales on the Subjective Well‐being under Neuroleptic treatment scale Short form‐Japanese version, the Schizophrenia Quality of Life Scale‐Japanese version, and the Brief Assessment of Cognition in Schizophrenia‐Japanese version, and in all factor scores on the Positive and Negative Syndrome Scale. Improvement in depressive symptoms with blonanserin treatment was positively correlated with improvements in subjective well‐being and subjective quality of life, as well as verbal memory. No significant changes were noted for any safety measure during the 1‐year study period. Conclusions Blonanserin was well tolerated and effective for the treatment of first‐episode schizophrenia in terms of subjective wellness, cognition, and a wide range of pathological symptoms. Further large‐scale studies are warranted to confirm our findings.